RNA expression profiling of renal allografts in a nonhuman primate identifies variation in NK and endothelial gene expression. Issue 6 (2nd February 2018) - Smith, R. N.; Adam, B. A.; Rosales, I. A.; Matsunami, M.; Oura, T.; Cosimi, A. B.; Kawai, T.; Mengel, M.; Colvin, R. B.
Abstract : RNA transcript expression estimates are a promising method to study the mechanisms and classification of renal allograft rejections. Here we use the Nanostring platform to profile RNA expression in renal allografts in a nonhuman primate (NHP), the Cynomolgus monkey. We analyzed protocol and indication 278 archival renal allograft samples, both protocol and indication from 76 animals with diagnoses of chronic antibody‐mediated rejection (CAMR), acute cellular rejection (TCMR), and MIXED (both CAMR and TCMR), plus normals and samples with no pathological rejection using a Cynomolgus‐ specific probe set of 67 genes. Analysis identified RNA expression heterogeneity of endothelial and NK genes within CAMR and TCMR, including the stages of CAMR. Three factors were partitioned into additional groups. One group with the longest allograft survival time is pure CAMR without NK or CD3. Three mixed groups show variation in NK and CD3. TCMR was split into 2 groups with variation in NK genes. Additional validation of the complete gene‐set correlated many of the genes with diagnoses of CAMR, MIXED, and TCMR rejections and with Banff histologic criteria defined in human subjects. These NHP data demonstrate the utility of RNA expression profiling to identify additional heterogeneity of endothelial and NK RNA gene expressions. Abstract : RNA expression profiling of renal allografts identifies heterogeneous expression of endothelial‐ and NK‐associated genes.